2022
DOI: 10.17159/sajs.2022/11994
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land-use changes on ant communities and the retention of ecosystem services in Rashad District, Southern Kordofan, Sudan

Abstract: The ecological consequences of biodiversity loss are usually the reduction of ecosystem functions. These responses, however, differ depending on the type of land-use change and the ecological setting. We investigated the impact of land-use type and ecosystem functions on the ant assemblage of Rashad District, Sudan. We analysed the effects of three different land uses (soy monoculture, pasture and organic production of vegetables) on the ant community by assessing ant composition in 176 different locations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
1
Order By: Relevance
“…Many studies have shown that the landscape is critical; it provides biodiversity and can increase the presence of predators of multiple taxa and consequently increase the ecological, biological control service (Eisawi et al, 2022). However, in this study, it is observed that the landscape does not influence the total number of preyed eggs and those preyed only by ants (Table 2).…”
Section: Discussioncontrasting
confidence: 54%
“…Many studies have shown that the landscape is critical; it provides biodiversity and can increase the presence of predators of multiple taxa and consequently increase the ecological, biological control service (Eisawi et al, 2022). However, in this study, it is observed that the landscape does not influence the total number of preyed eggs and those preyed only by ants (Table 2).…”
Section: Discussioncontrasting
confidence: 54%